2012
DOI: 10.4269/ajtmh.2012.11-0746
|View full text |Cite
|
Sign up to set email alerts
|

House Infestation Dynamics and Feeding Sources of Triatoma dimidiata in Central Veracruz, Mexico

Abstract: Abstract. Chagas disease is endemic in the state of Veracruz, Mexico, and we investigated here the dynamics of house infestation by Chagas disease vectors to understand disease transmission and design effective control interventions. Bug collections in 42 rural villages confirmed the widespread distribution of Triatoma dimidiata in central Veracruz. Unexpectedly, collection data further indicated a clear pattern of seasonal infestation by mostly adult bugs. Analysis of feeding sources with a polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
3
26
0
2
Order By: Relevance
“…28 Previous studies identified human blood as a common food source for T. dimidiata in the domestic environment, and an important food source in peridomestic environments: 63 ; and 87.5% of bugs collected indoors and 25% of the bugs collected outdoors in Veracruz, Mexico. 31 We detected human blood in almost 40% of bugs at the beginning of this study, and this was reduced considerably ( 10%) after the control interventions. These data suggest that T. dimidiata will often take human blood when it's available, and that the interventions have successfully reduced human-vector contacts.…”
Section: Discussionmentioning
confidence: 91%
“…28 Previous studies identified human blood as a common food source for T. dimidiata in the domestic environment, and an important food source in peridomestic environments: 63 ; and 87.5% of bugs collected indoors and 25% of the bugs collected outdoors in Veracruz, Mexico. 31 We detected human blood in almost 40% of bugs at the beginning of this study, and this was reduced considerably ( 10%) after the control interventions. These data suggest that T. dimidiata will often take human blood when it's available, and that the interventions have successfully reduced human-vector contacts.…”
Section: Discussionmentioning
confidence: 91%
“…This is consistent with previous reports of high prevalences in blood banks located in these regions . No significant difference was observed in the Papaloapan, Los Tuxtlas, and Olmeca regions, as assessed by chi‐square test, although these regions showed high percentages of confirmed cases and have been previously reported as high‐risk municipalities . For example, the municipality of Tezonapa (located in mountains region) was previously reported to have a prevalence of up to 16.8% in an open population .…”
Section: Discussionmentioning
confidence: 76%
“…). This could be related to vector behavior, as Triatoma dimidiata conducts seasonal housing invasions in rural areas of Mexico in April, May, and June . This could logically increase the number of vector‐borne infections during these months.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in Mexico have indicated that the domiciliary population of T. dimidiata could increase during the hot and dry season in April-June (Dumonteil et al 2002, Torres-Montero et al 2012. Such seasonal variation is also observed in Jalapa, according to the number of bugs reported by the communities (Fig.…”
Section: Discussionmentioning
confidence: 81%